The Role of Product Owner: Duties, Effects and Qualities in Software Development in Iceland - Pétur Bjarni Pétursson 1988- (2020)
Agile software development methods such as Scrum have been widely used since 2001(Beck et al., 2001). Scrum is a framework that defines various roles and methods to successfully develop a software product. One of those roles is the Product Owner, whose responsibilities include maximizing the product value. This study researched the role of Product Owner in the context of software development in Iceland. The research questions sought to answer what activities Product Owners performed, how they affected development cost, time and scope, what methods they used for affecting product value, similarities with other roles and what skills or qualities were expected of a Product Owner. The study was carried out using qualitative research methods, data gathered by interviews and observations and grounded theory used in data analysis. The results found that in addition to activities established in theory the Product Owners were involved in supervising the progress of product development, a duty traditionally done by a Scrum Master. The Product Owners affected time and scope more than cost, and the study identified novel skills which were associated with the Product Owner such as technical skills, domain knowledge and creativity. Agile aðferðir við hugbúnaðarþróun eins og Scrum hafa verið mikið notaðar síðan árið 2001 (Beck et al., 2001). Scrum er aðferðafræði sem skilgreinir ýmis hlutverk og aðferðir til að þróa hugbúnaðarvöru á sem skilvirkastan hátt. Eitt þeirra hlutverka er vörustjóri (enska Product Owner), sem ber ábyrgð á því að hámarka virði vörunnar. Þessi rannsókn skoðaði hlutverk vörustjóra í samhengi hugbúnaðarþróunar á Íslandi. Rannsóknarspurningarnar sem leitað var svara við voru hvaða verkefnum vörustjóri sinnir, hvernig vörustjórar hafa áhrif á þróunarkostnað, -tíma og -umfang, hvaða aðferðum þeir beita til að hafa áhrif á virði vöru, líkindi með öðrum störfum og hvaða hæfni eða hæfileika er búist við að vörustjóri hafi yfir að ráða. Rannsóknin var framkvæmd með eigindlegum rannsóknaraðferðum, gögnum safnað ...